PENGGUNAAN INTERACTIVE FLAT PANEL (IFP) DALAM UPAYA MENINGKATKAN MUTU PEMBELAJARAN IPAS (STUDI KASUS DI SDN 2 BABAKAN) - Warta, Waska; Rahmawati, Ati; Novtiansyah, Novan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digital transformation in education demands massive technological adaptation to improve the quality of learning. This study aims to analyze the effectiveness of management in utilizing the Interactive Flat Panel (IFP) as a learning medium for Natural and Social Sciences (IPAS) in elementary schools using the POAC (Planning, Organizing, Actuating, and Controlling) framework. Employing a qualitative approach with a comparative case study method, data were collected through in-depth interviews, participant observation, and documentation studies in elementary education institutions in Purwakarta Regency. The results indicate that the effectiveness of improving the quality of IPAS learning heavily relies on systematic management integration. A mature planning phase in developing digital teaching modules, adaptive scheduling and standard operating procedures organization, student-centered learning implementation through multi-touch features and virtual laboratories, as well as periodic academic supervision, are proven to optimize school technological assets. Well-managed technology integration not only enhances students' cognitive engagement in abstract science materials but also directly contributes to the improvement of student learning outcomes and digital literacy skills.